Transcranial magnetic stimulation in pontine infarction: correlation to degree of paresis. Issue 4 (April 1992) - Ferbert, A; Vielhaber, S; Meincke, U; Buchner, H
Abstract : Transcranial magnetic stimulation was performed in 20 patients with pontine infarction who had initially some degree of hemiparesis. Only patients with a well defined lesion on magnetic resonance imaging that was appropriate for the neurological signs were included. Recordings were made from the abductor pollicis brevis muscle (APB) bilaterally. The degree of hand paresis was estimated clinically and related to the following parameters: central motor conduction time (CMCT), interside latency difference of total latency, and amplitude ratio of affected to unaffected side. Increasing degree of paresis was associated with increasing latency parameters and decreasing amplitude ratio. In the four patients with severe paresis a low amplitude response could be evoked and CMCT was delayed by up to 10 ms. When the paresis had resolved at the time of transcranial magnetic stimulation CMCT was normal. However, amplitude ratio was less than 100% in all but one patient, with most of the values ranging between 40% and 60%, which indicates a subclinical pyramidal tract lesion. Median nerve sensory evoked potentials (SEP) and related interside latency difference to amplitude ratio N20/P25 were also recorded. In contrast to TCMS, decreased amplitude ratio of SEP was not associated with delayed latency. Clinically, the mild degree of and good recovery from paresis in ventral pontine infarction was remarkable.